Toxic Gas Response for Nanostructured Cobalt Oxide Thin Films - A. Hamdan, suhad; M. Ali, Iftikhar; M.Ibrahim, Isam (Iraqi Journal of Physics, 2021)
The gas sensing properties of undoped Co3O4 and doped with Y2O3 nanostructures were investigated. The films were synthesized using the hydrothermal method on a seeded layer. The XRD, SEM analysis and gas sensing properties were investigated for the prepared thin films. XRD analysis showed that all films were polycrystalline, of a cubic structure with crystallite size of (12.6) nm for cobalt oxide and (12.3) nm for the Co3O4:6% Y2O3. The SEM analysis of thin films indicated that all films undoped Co3O4 and doped possessed a nanosphere-like structure. The sensitivity, response time and recovery time to H2S reducing and NO2 oxidizing gases were tested at different operating temperatures. The resistance changed with exposure to the test gas. The results revealed that the Co3O4:6%Y2O3 possessed the highest sensitivity around 90% (at room temperature) and 62.5% (at 150 oC) when exposed to the reducing gas H2S and oxidizing gas NO2, respectively with 0.8sec for both recovery and response times.